ASSESS THE PREVALENCE OF RESPIRATORY PROBLEM AND KNOWLEDGE ON HEALTH EFFECTS OF PEOPLE RESIDING NEAR QUARRY - M.a., Sahbanathul Missriya; S., Subashini (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: In the quarry area, there are various suspended particulate matters are mixed with the ambient air in and around. People residing near to that quarry areas are exposed to hazards through the inhalation of airborne particulates. Due to that, the respiratory problems are very common among them. The study was aimed to assess the prevalence of respiratory problems and determine the level of knowledge on health effects of people living near to quarry at Kundrathur. Methods: Descriptive cross-sectional research design was adopted. Convenient sampling technique was used to select 60 people residing near the quarry. The data was collected by using structured questionnaire through face to face interview. The collected data was organised and analysed by descriptive and inferential statistics. Results: The study findings showed that the prevalence of respiratory problems was high 41(68.33%) among people residing near the quarry and 19(31.66%) people did not show any signs and symptoms of respiratory problems. The knowledge regarding health effects was showing that 39(65%) people had inadequate knowledge, 21(35%) people had the moderate knowledge, and none of the people had adequate knowledge. Conclusion: The study concluded that, though there was the prevalence of respiratory problems and most of them had inadequate knowledge on health effects and there is a need to advise the people about safety from respiratory diseases.